PROSPECTS FOR IMPROVING THE BIOLOGICAL VALUE OF BISCUIT PRODUCTS IN RESTAURANTS - Koshel, O. Yu.; Mazurenko, I. K.; Sabadash, S. M. (Bulletin of Sumy National Agrarian University. The series: Mechanization and Automation of Production Processes, 2023)
The article reflects the theoretical and experimental justification of the use of protein-enriched raw materials in the technology of semi-finished biscuits. Biscuit semi-finished products are considered products that contain a small amount of protein and a large amount of carbohydrates in their nutritional composition. Having analyzed the review of literary sources, it was determined that among the variety of raw materials that are added to the technology of semi-finished biscuits, it would be relevant to use raw materials that have a significant amount of easily digestible proteins and are freely available for restaurants. Spirulina powder was used as an innovative raw material. Spirulina powder in concentrations of 5.0…15.0% was added to the recipe of the semi-finished round biscuit. To determine the exact concentration of the amount of powder, first of all, the main structural-mechanical and organoleptic properties of the biscuit semi-finished product were studied. To determine the structural and mechanical properties of the finished product, the viscosity of the dough with the addition of an innovative raw material, i.e. spirulina powder, was tested. It is important that the viscosity of the dough affects the foaming ability of the dough, and is one of the main indicators for biscuits. Given that a new raw material is being introduced, checking the viscosity index is necessary. To determine the organoleptic indicators, the method of sensory evaluation of the baked semifinished product was used. According to the results of the study of the structural and mechanical properties and organoleptic indicators of the products, the innovative semi-finished biscuit with the addition of spirulina powder in the amount of 10.0% had the best indicators in comparison with other samples. However, according to organoleptic indicators, all samples had a sea smell, which is not quite rational in the technology of semi-finished biscuit Therefore, in the future, in order to determine the exact concentration of spirulina powder, it is important to conduct a general assessment of the quality of the semi-finished biscuit among the consumers of the restaurant industry.